The Implementation of Merdeka Curriculum to Realize Indonesia Golden Generation: A Systematic Literature Review - Syahrir Syahrir; Pujiriyanto Pujiriyanto; Musdalifa Musdalifa; Sakinah Fitri (STAI Hubbulwathan Duri, 2024)
The Merdeka Curriculum serves as a pivotal framework for cultivating a resilient and socially adept golden generation, aligning with the cherished principles of Pancasila. This study endeavors to evaluate the efficacy of the Merdeka Curriculum in fostering Indonesia's golden generation, gauging its influence on soft skills and character development as per the Pancasila learner profile, and identifying obstacles encountered during its implementation across diverse educational settings in Indonesia. Employing a systematic literature review approach following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, this research sourced pertinent articles from the